Endoscopic resection using an over-the-scope clip for duodenal neuroendocrine tumors - Tashima, Tomoaki; Ryozawa, Shomei; Tanisaka, Yuki; Fujita, Akashi; Miyaguchi, Kazuya; Ogawa, Tomoya; Mizuide, Masafumi; Mashimo, Yumi; Kawasaki, Tomonori; Yasuda, Masami (Endoscopy International Open, 2021)
Background and study aims Endoscopic resection of duodenal neuroendocrine tumors (DNETs) remains controversial, and its indications are still unclear. This study aimed to evaluate short-term outcomes of a newly developed endoscopic muscularis resection (EMR) method that utilizes an over-the-scope clip (OTSC), termed EMRO, for treating DNETs.Patients and methods In total, 13 consecutive patients with 14 small (≤ 10 mm) DNETs who underwent EMRO from September 2017 to March 2020 were retrospectively enrolled. EMRO was performed by a single experienced endoscopist. Patients’ characteristics and treatment outcomes were assessed.Results The En bloc and R0 resection rates were 100 % (14/14) and 92.9 % (13/14), respectively. The median pathological resected specimen size was 10 mm, with a median pathological resected tumor size of 6 mm. During the EMRO procedure, there was no occurrence of misplacement of the OTSC to the target lesion. With respect to the pathological resection depth, nine cases (64.3 %) and five cases (35.7 %) were categorized as deep submucosal resection and muscularis resection, respectively, whereas no case was categorized as full-thickness resection. There were no intraoperative or delayed perforations. However, delayed bleeding occurred in two cases. At a median follow-up of 12 months (range 7–36) after EMRO, there was no incidence of local recurrence. At the first follow-up endoscopy performed at 6 months after EMRO, the OTSC was retained in place in two of 14 DNETs (14.3 %).Conclusions EMRO can be performed safely, by an experienced endoscopist, for small (≤ 10 mm) DNETs.